2016
DOI: 10.1002/smi.2684
|View full text |Cite
|
Sign up to set email alerts
|

Approach Behaviour, Stress and Substance Use in Young Adults

Abstract: We investigated the interaction between approach behaviours (measured through performance on a resource-gathering task) and self-reported global life stress to predict substance use. Our hypothesis that high levels of approach behaviour in combination with high life stress would predict elevated substance use was guided by the reinforcement sensitivity theory (Gray & McNaughton, ). Ninety-three young adult students (61 women and 32 men) completed a computerized resource-gathering task and questionnaires assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Moreover, a meta-analysis systematically reviewing 204 studies found that BIS could significantly predict depression (β = 0.37) and anxiety (β = 0.35), while BAS only significantly predicting depression (β = −0.07) ( Benjamin et al, 2020 ). Hinnant et al (2017) indicated that BAS was positively related to substance use for individuals with high-level stress. However, under the stress, it generally leads to the enhanced avoidance, and induces approach in individuals prone to aggression ( Vogel and Schwabe, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a meta-analysis systematically reviewing 204 studies found that BIS could significantly predict depression (β = 0.37) and anxiety (β = 0.35), while BAS only significantly predicting depression (β = −0.07) ( Benjamin et al, 2020 ). Hinnant et al (2017) indicated that BAS was positively related to substance use for individuals with high-level stress. However, under the stress, it generally leads to the enhanced avoidance, and induces approach in individuals prone to aggression ( Vogel and Schwabe, 2019 ).…”
Section: Introductionmentioning
confidence: 99%